La frontière roumano-ukrainienne et le poids réel de la question des minorités - Frédéric Beaumont (Cybergeo)
The border which currently divides Romania and Ukraine is due to the soviet decision to annex North Bukovina and Bassarabia in 1940. After the fall of the Soviet Union, the Romanian leaders tried to assert their rights to these lands, from which they had been despoiled. The question of the minorities was still at the centre of the debate, even if the real stake in the regular Romanian-Ukrainian negotiations seems actually to have been the “Snakes’ Island”, an unoccupied sandbank off the Danube Delta, which is close to territories of important oil resources.